2020
DOI: 10.1002/andp.202000078
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Chiral Metasurfaces for Second‐Harmonic Generation with Strong Circular Dichroism

Abstract: Dielectric chiral metasurfaces can generate harmonic waves with high efficiency and strong circular dichroism (CD), when they are supported by metallic substrates. Numerical results show that the second-harmonic generation (SHG) efficiency of about 10 −3 % for a peak pump intensity of about 5 GW cm −2 can be achieved in the blue-UV, and the SHG CD reaches up to about 1.8, from a metasurface of Z-shaped lithium niobate nanoantenna array supported by gold substrate. Highly efficient and strong circular dichroic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Figure 6b shows the wavelength dependence of the SHG conversion efficiency (𝜂) for RCP and LCP, which is calculated as 𝜂 = P SH ∕P FH . The efficiency can reach ≈1.35 × 10 −2 % for RCP pumping at 1.334 μm, which is larger than the efficiency that was previously reported, [15] and the peak position is consistent with (E y /E 0 ) 2 in Figure 3d. For LCP pumping, the SHG efficiency is only 8 × 10 −4 % which is attributed to the effective suppression of the quasi-BICs and low internal field enhancement.…”
Section: Nonlinear Responses Of Chiral Ln Metasurfacesupporting
confidence: 86%
See 3 more Smart Citations
“…Figure 6b shows the wavelength dependence of the SHG conversion efficiency (𝜂) for RCP and LCP, which is calculated as 𝜂 = P SH ∕P FH . The efficiency can reach ≈1.35 × 10 −2 % for RCP pumping at 1.334 μm, which is larger than the efficiency that was previously reported, [15] and the peak position is consistent with (E y /E 0 ) 2 in Figure 3d. For LCP pumping, the SHG efficiency is only 8 × 10 −4 % which is attributed to the effective suppression of the quasi-BICs and low internal field enhancement.…”
Section: Nonlinear Responses Of Chiral Ln Metasurfacesupporting
confidence: 86%
“…For the RCP incident, although the maximum field enhancement occurs in the vicinity of the bar tips, there is still an enhancement of nearly 20 times inside the elliptical LN bars, which is significantly higher than that reported in the literature. [15] Moreover, by comparing Figure 4a,c and Figure 4b,d, it can be observed that the field enhancement effect is close to 0 for LCP incidence, which indicates that the metasurface field enhancement strongly depends on the handedness of the incident light polarization owing to the strongly polarization-dependent strength quasi-BIC modes excited on the LN metasurface, and also provides a method for the strong nonlinear CD implementation.…”
Section: Linear Responses Of Chiral Ln Metasurfacementioning
confidence: 74%
See 2 more Smart Citations
“…8). Ensuring high index contrast between the nanoparticles and substrates 8 or using metallic substrates [9][10][11] prevent the mode leakage and support strong eld connement even with the lower-index materials.…”
Section: Introductionmentioning
confidence: 99%